"Mga bata sa tahanan" an evaluative study of a child-care strategy - Pineda, Josefina D.; Quieta, Romeo C. (Philippine Journal of Psychology, 1982)
The strategy of replacing institutional care for children with family placement has been undertaken by the Kaisahang Buhay Foundation with several child-welfare institutions. It emphasizes the family as the primary instrument in developing the child. Instead of focusing on the child alone, the strategy provide/extends basic socio-economic and psychological services to the whole family. The study evaluates the effects of such a strategy, in contrast to institutionalized child-care. Essentially, there are two focused on the change processes involved in the implementation of the strategy, on one hand, and changes in the socio-economic and interpersonal relationships of the family, on the other. The results of the evaluative study showed that the KBF Home-care project is effective. The families generally agreed that the benefited not only from the financial assistance that was extended but also from the other family services that were delivered to them. As against institutional care, the cost-effective benefits of the project are favorable. The study concluded that institutional care still has some merits in terms of having a supportive role in the spectrum of family child welfare services for certain deprived families.There are some factors, too, that impeded the application of the KBF approach. The main factor is that the KBF financial subsidy has been found to be very inadequate by the families.The study also gives recommendations for both of the institutional care and the home-care approaches. There must be an upgrading of the quality of institutional care and there must be a further strengthening of home and family care to provide the suitable atmosphere for child-growth and development.